Implementaciòn del proceso contable y su incidencia en la gestión financiera en “Plomeelec”, del cantón Macará, provincia de Loja, periodo noviembre a diciembre de 2015 - Valarezo Astudillo, Mónica Beatriz (2016)
The item entitled Implementation ACCOUNTANT PROCESS AND ITS IMPACT ON FINANCIAL MANAGEMENT "PLOMEELEC" Canton MACARÁ, Loja province, PERIOD November to December 2015, was conducted in order to provide a fundamental tool for the right financial development, in order to know the movement of its main accounts for the periods analyzed, they are designed to benefit business and thus meet the needs of its customers. Fulfilling the goals outlined in this thesis, a logical and orderly order, which starts from the record of purchases, sales and deductions, then the Chart of Accounts, State Initial situation was developed followed; the memorandum over a period of two months, to proceed to Journalize and develop accounting entries in the Daybook; the elderly, trial balance, worksheet, the respective adjustments and finally all this information in condensed financial statements was made. With the results we have concluded that the owner of "PLOMEELEC" does not maintain a clear accounting system, which helps the economic management of it, it does not allow a proper record of transactions that day are given day , to obtain the financial statements and tax liabilities reliable Finally to take into account the work done in this thesis, in order for there to be a timely and reliable economic information for proper decision making for the benefit of their own development is recommended.